A Conceptual Framework for Smart Hospital towards Industry 4.0 - MohammadHossein Ronaghi (Tehran University of Medical Sciences, 2020)
Background: The fourth industrial revolution consists of combining network devices with cloud computing methods and analyzing large data and artificial intelligence, which makes it possible to call such an infrastructure smart. In a Smart Hospital, all things and devices are designed to be connected and integrated, thus achieving better patient care, increasing efficiency and reducing time waste. Therefore, the aim of this paper was to recognize the components of smart hospital based on disruptive technologies of industry 4.0. Materials and Methods: This applied research has been done in two phases using qualitative approach in winter 2019. In the first step, the components of smart hospital were recognized from previous studies. In the second step, research experts evaluate conceptual model by Delphi method. The expert panel consists of 15 individuals active in information technology in healthcare according to targeted sampling.  Results: According to research results the main components of smart hospital are eight technologies: Internet of things technology, robotic, blockchain technology, cloud computing, big data, augmented and virtual reality technology, additive manufacturing and artificial intelligence. Conclusion: According to components of smart hospital, Hospitals managers should equip their organization and adopt process and equipment by disruptive technologies. Due to sanctions, investment in Iranian knowledge-based companies active in new technologies field and Joint venture with them can be a suitable solution for healthcare policymakers.